Direct ammonium recovery from the permeate of a pilot-scale anaerobic MBR by biochar to advance low-carbon municipal wastewater reclamation and urban agriculture - Zhang, Xiaoyuan (2023)
The rapidly evolving global climate change has an unprecedented impact sustainable water supply, but also challenges and water shortage global food security. In such a dynamic situation, this study explored direct recovery of ammonium from the effluent of a pilot-scale anaerobic membrane bioreactor (AnMBR) treating actual municipal wastewater via biochar adsorption, while the use of produced ammonium-loaded biochar for urban agriculture was also demonstrated. Results showed that modified biochar could remove almost all ammonium in the pilot AnMBR permeate at an empty bed contact time of 30 mins. Results showed that ammonium extracted from the ammonium-loaded biochar could promote the germination of Daikon radish seeds. It was further observed that the fresh weight of Pak Choi (a typical leafy vegetable) planted in the soils augmented with the ammonium-loaded biochar was 42.5 g per vegetable versus 18.5 g per vegetable in the control, indicating a 130 % of increase in the Pak Choi productivity. In addition, the Pak Choi in grown the ammonium-loaded biochar augmented soils appeared to be much bigger with larger leaves compared to the control. It was also worth to note that the ammonium-loaded biochar could significantly stimulate the root development of Pak Choi, i.e., 20.7 cm over 10.5 cm obtained in the control. More importantly, the amount of carbon emission reduced through returning ammonium-loaded biochar to urban agriculture could offset the treatment process-associated direct and indirect carbon emission.